Computer Simulations Support a Morphological Contribution to BDNF Enhancement of Action Potential Generation - Galati, Domenico F.; Hiester, Brian G.; Jones, Kevin R. (Frontiers in Cellular Neuroscience, 2016)
Abstract Brain-derived neurotrophic factor (BDNF) regulates both action potential (AP) generation and neuron morphology. However, whether BDNF-induced changes in neuron morphology directly impact AP generation is unclear. We quantified BDNF’s effect on cultured cortical neuron morphological parameters and found that BDNF stimulates dendrite growth and addition of dendrites while increasing both excitatory and inhibitory presynaptic inputs in a spatially restricted manner. To gain insight into how these combined changes in neuron structure and synaptic input impact AP generation, we used the morphological parameters we gathered to generate computational models. Simulations suggest that BDNF-induced neuron morphologies generate more APs under a wide variety of conditions. Synapse and dendrite addition have the greatest impact on AP generation. However, subtle alterations in excitatory/inhibitory synapse ratio and strength have a significant impact on AP generation when synaptic activity is low. Consistent with these simulations, BDNF rapidly enhances spontaneous activity in cortical cultures. We propose that BDNF promotes neuron morphologies that are intrinsically more efficient at translating barrages of synaptic activity into APs, which is a previously unexplored aspect of BDNF’s function.